2015
DOI: 10.1002/cncr.29528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis C virus eradication on hepatocellular carcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death in the world. Infection with the hepatitis C virus (HCV) represents one of the most common risk factors for HCC development and cases of HCV-related complications have been rising over the last two decades. Though the standard of HCV therapy has been interferon (IFN)-based for many years, the therapeutic revolution spurred by the development of direct-acting antivirals (DAAs) promises to usher in a new era in which chronic hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 68 publications
2
69
0
1
Order By: Relevance
“…1 We agree that the high upfront costs of direct-acting antivirals have proved to be a major challenge for payers. However, a number of independent studies have demonstrated that all-oral DAA regimens, even at their wholesale prices, are cost-effective under most circumstances.…”
Section: Funding Supportmentioning
confidence: 89%
See 1 more Smart Citation
“…1 We agree that the high upfront costs of direct-acting antivirals have proved to be a major challenge for payers. However, a number of independent studies have demonstrated that all-oral DAA regimens, even at their wholesale prices, are cost-effective under most circumstances.…”
Section: Funding Supportmentioning
confidence: 89%
“…1 First, there is a very substantial cost and hope cannot replace postmarketing studies. For example, sofosbuvir, which costs approximately $1000 per day and $84,000 for the full 12-week treatment, will increase the Medicare Part D Prescription Drug Benefit by $6.5 billion in 2015, an overall 8% increase in spending.…”
mentioning
confidence: 99%
“…We appreciate the interest of Testino et al in our recent review 1 . We agree that the risk of hepatocellular carcinoma (HCC) remains elevated in patients who achieve sustained virologic response (SVR), particularly in those who already have cirrhosis.…”
mentioning
confidence: 87%
“…26 It is important to note that despite the decrease in HCC risk in patients achieving a sustained virologic response, patients with advanced liver fibrosis still remain at long-term risk for HCC. 27 This means that patients with HCV infection will require continuous monitoring, and future studies will need to validate any decrease in the incidence of HCC.…”
Section: Secondary Preventionmentioning
confidence: 99%